AEROBIC AND ANAEROBIC CO-CULTIVATION OF MICROALGAE WITH OIL PALM EMPTY FRUIT BUNCHES FOR BIOMETHANE PRODUCTION AND PALM OIL MILL EFFLUENT TREATMENT - AHMAD, ASHFAQ AHMAD (2013)
There is an increasing interest in alternative renewable sources of biofuels due to increased demand for energy worldwide. In Malaysia, palm oil industry is one of the leading industries which produce more than 13 million tonnes ofcrude palm oil annually, covering 11% ofland area. The production of such amount also result in large amounts solid wastes and of palm oil mill effluent (POME), estimated at nearly three times the quantity of crude palm oil. POME is a highly polluting wastewater due to its high chemical oxygen demand (COD), biochemical oxygen demand (BOD) and minerals such as nitrogen and phosporus which can cause severe pollution to the environment and water resources. Anaerobic digestion can be used for POME treatment, but with greater emphasis on capturing the methane gas released as aby-product. This can be achieved by co-cultivation ofmicroalgae with oil palm empty bunches (OPEFB).